Principles for transmedia educational practices under the academic literacy mode - Silva, Alana Silveira da; Fischer, Adriana; Pottmeier, Sandra (Revista Hipótese, 2024)
This article seeks to discuss principles for transmedia literacy practices from the perspective of the academic literacy model. How can literacy practices involving multiple languages (multimodal) contribute to reading and writing development for students in Higher Education? Thus, a qualitative meta-analysis of 20 articles from the Web of Science database was performed. On the platform, the criteria of publication date between 2017 and 2021, articles available in the main collection, which have open access, and the terms transmedia and education were used in the search for subjects for the selection of the research corpus. The data showed that in order to produce educational practices with transmedia, it is necessary to create didactic materials that support teachers, activities that provide dialogue with different voices, and discursive genres directed to academic literacy. Thus, it is considered that continuing education for teachers and the production of didactic material is necessary, envisioning pedagogical activities with technologies, transmedia, and media platforms, among others, in formal teaching contexts.